Effect of building importance factor on seismic performance of rc frame type shopping malls subjected to pulse-like records. (December 2021) - Güllü, Ahmet; Karameşe, Genco
Highlights: The seismic performances of the shopping malls were evaluated considering the effect of the building importance factor. The analyses were performed using three-dimensional buildings rather than 2D frames. The studied buildings were subjected to pulse-like records. Abstract: Since they offer many alternatives for shopping, eating, resting, etc. many people spend a considerable time in shopping mall buildings. Therefore, this type of building is increasing rapidly. The increment rate was almost three in Turkey for the last decade. The recently released seismic code of the country has some serious alterations such as increased seismicity of some regions and reduced performance level limits of structural members. Besides, the building importance factor ( I ) of the shopping malls was defined clearly to be 1.2 whereas some shopping malls were designed considering I = 1.0 and constructed before 2018. Therefore, seismic performances of the shopping malls became questionable according to the code. In this study, seismic performances of two existing shopping mall buildings, which were designed and constructed by considering I = 1.0, are investigated based on the recently released seismic code and nonlinear analyses in which the utilized records were scaled considering I = 1.2 . The results showed that the increased seismicity and reduced performance level limits may lead to excessive story drifts and plastic rotations for some records. However, the mean value of the analysis results satisfies the life safety (LS) performance level. Therefore, the importance factor might be suggested to be 1.0 for shopping malls close to the faults to avoid an unnecessary increment of the initial cost.